Breaking barriers : travel and the state in early modern Japan - Vaporis, Constantine Nomikos, 1957- (Harvard East Asian monographs, 1994)
Travel in Tokugawa Japan was officially controlled by bakufu and domainal authorities via an elaborate system of barriers, or sekisho, and travel permits; commoners, however, found ways to circumvent these barriers, frequently ignoring the laws designed to control their mobility. In this study, Constantine Vaporis challenges the notion that this system of travel regulations prevented widespread travel, maintaining instead that a "culture of movement" in Japan developed in the Tokugawa era.